Rehabilitation and Chronic Care 2017
DOI: 10.1183/1393003.congress-2017.pa3452
|View full text |Cite
|
Sign up to set email alerts
|

Palliative and end of life care conversations in COPD - a systematic literature review

Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic life-limiting disorder characterised by persistent airflow obstruction and progressive breathlessness. Discussions/conversations between patients and clinicians ensure palliative care plans are grounded in patients' preferences. This systematic review aimed to explore what is known about palliative care conversations between clinicians and COPD patients.A comprehensive search of all major healthcare-related databases and websites was performed following… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(38 citation statements)
references
References 28 publications
(65 reference statements)
0
38
0
Order By: Relevance
“…It also seems that the patients' voice within the assessment of treatment-trade-off is not always taken into account. This finding is not surprising, barriers to starting conversation about the end of life are numerous and divers [31,40]. One specific barrier described by our respondents is that they did not believe to be the right person to discuss the end of life with patients.…”
Section: Main Findings and Comparison With Other Studiesmentioning
confidence: 66%
“…It also seems that the patients' voice within the assessment of treatment-trade-off is not always taken into account. This finding is not surprising, barriers to starting conversation about the end of life are numerous and divers [31,40]. One specific barrier described by our respondents is that they did not believe to be the right person to discuss the end of life with patients.…”
Section: Main Findings and Comparison With Other Studiesmentioning
confidence: 66%
“…The degree to which palliative care consultations occurred were not captured within this study but a recent systematic review found that current practices for AECOPD patients could improve considerably. 20 It would appear reasonable to include palliative care as an important adjunct to the management of AECOPD in ICU whenever LOMT has been decided.…”
Section: Respectively Decreased Pao 2 and Hco 3 − And Increasedmentioning
confidence: 99%
“…18,19 Different views between intensivists and respiratory physicians on the likely clinical trajectory of AECOPD and the need for ICU admission are not uncommon. Transparent and honest discussion between healthcare professionals, patients and their relatives about goals of treatment is to be encouraged, and limitations of medical therapy and palliative care, even while active treatment is ongoing, 20 should be considered. Compared to patients with cancer, patients with AECOPD receive less palliative care and are more likely to succumb to their disease following aggressive and invasive treatments with an admission to ICU.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is not yet clear how palliative care can be successfully integrated into COPD-care. At the moment, discussions on prognosis, goals of care and advance care planning rarely occur or only at a very late stage of the disease [9]. Neither are patients with COPD regularly referred to specialist palliative care [10].…”
Section: Introductionmentioning
confidence: 99%